Spectral Angle Mapper as a Tool for Matching the Spectra in Hyperspectral Processing (Advances in Military Technology, 2022)
The article deals with analysis of Spectral Angle Mapper (SAM) as a tool for matching the separated endmembers with pure spectra from databases. The analysis of SAM is provided in three spectral regions: VIS, IR and VIS+IR together. Three kinds of available influences are analysed: additive noise, constant offset and slant offset.
Keywords: hyperspectral imaging; noise; offset; spectral angle mapper